Experimental Autoimmune Encephalomyelitis as a Testing Paradigm for Adjuvants and Vaccines - Libbey, Jane E. (2010)
Experimental autoimmune encephalomyelitis (EAE) is an experimental model for multiple sclerosis. EAE can be induced by inoculation with central nervous system (CNS) proteins or peptides emulsified in complete Freund’s adjuvant. Protection from EAE, enhancement of EAE or subclinical priming for EAE can occur as a result of either live viral infection or DNA immunization with molecular mimics of CNS proteins or peptides. Here we review the published data describing modulation of EAE through administration of various CNS proteins/peptides introduced via live virus or plasmid DNA and modulation of EAE through choice of adjuvant (immunostimulating agents).